Extarction of wind power with battery energy storage for critical load condition in grid connected system - Naveen, M.Srinivasa; Reddy, N.Nageswara (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
In the grid, renewable resources are connected to extract more power. This adds more problems to grid, such as voltage fluctuations and distortions. The proposed micro wind energy conversion system with battery energy storage is used to exchange the controllable real and reactive power in the grid and to maintain power quality at the point of common coupling (PCC). In this scheme inverter is controlled by the hysteresis current controller to achieve the faster dynamic switch over for the support of critical load. The reference signals are derived from one of the phase voltage. The main objective of the proposed control is the three phase supply currents both in its waveform, magnitude and phase to follow three phase reference signals. When this is achieved, ideally the supply current will then be always sinusoidal, with robust control over its magnitude and phase, irrespective of the harmonics and unbalance of the load demand or the supply voltage system. This confirms nearly unity power factor on supply side with active and reactive power support from the wind turbine side. The battery storage with micro wind energy generation system will obtain the output waveform by injecting (or) absorbing reactive power and enable the real power flow required by the load. The generated power can be stored in the batteries at low power demand hours. This scheme can be operated as a standalone system in case of grid failure like a uninterrupted power supply.